Community Empowerment with Stunting Filters to Create Healthy Families - Solikhah, Fitriana Kurniasari; Astuti, Erlina Suci; Ernawati, Naya; Arif, Taufan; Tyas, Maria Diah Ciptaning; Hamarno, Rudi; Wiyono, Joko; Subekti, Imam (Tarqabin Nusantara Group, 2023)
Stunting is a condition where a child experiences growth disorders, so that the child's height does not correspond to his age, as a result of chronic nutritional problems, namely lack of nutritional intake for a long time (Ministry of Health, 2020). The results of the 2018 Regional Health Research (Riskesdas 2018) show that toddlers in Indonesia aged 0-23 months still experience shortness of breath or very shortness of breath. This shows that there is a bright spot in the implementation of intervention programs in accelerating the reduction of stunting rates which cannot be separated from the cooperation of every existing element. The difference in the average knowledge of pre- and post-education cadres providing education to improve care for low birth weight babies was obtained by a mean pre-education value of 2.60 and a mean post-education value of 1.40. The standard deviation value for pre-training is 0.308 and post-training is 0.40. The Wilcoxon z value is -4.102. The statistical test results of the Wilcoxon signed rank test obtained a value of p = 0.000 (p < 0.05). Thus, it can be concluded that there is a significant difference between before and after training in cadres' knowledge about early detection of stunting in toddlers. The community service program to assist families at risk of stunting is a new breakthrough in determining effective and integrated, community-based strategies to reduce the risk of stunting.